Redressing Science Learning Through Supporting Language: The Biology Credit Recovery Course. (December 2019) - Gomez, Kimberley; Gomez, Louis M.; Cooper, Benjamin; Lozano, Maritza; Mancevice, Nicole
Annually, thousands of U.S. students fail high school introductory biology. The language demands of biology are large, and science teachers are often unprepared to support students' language needs. Here, we describe a 4-week summer high school introductory biology course executed in a large West Coast city. Our aim was to help 33 students recover their biology credit. A centerpiece of the 4-week course was the embedding of metacognitive language support tools in class lectures and assessments. Of 29 regular attendees, 28 passed with a C or better. Student science learning was reliably associated with use of the language support tools.